Broken things - Oliver, Lauren, 1982- (New York : HarperCollins Children's Books, 2018)
Everyone thinks Mia and Brynn killed their best friend after becoming obsessed and delusional over a novel, but on the anniversary of their friend's death a discovery pulls them back together to find out what actually happened that night.
Keywords: Murder -- Fiction; Friendship -- Fiction; Mystery and detective stories; Homicide -- Fiction; Friendship -- Fiction; Mystery fiction